Effect of atorvastatin on muscle symptoms in coronary heart disease patients with self-perceived statin muscle side effects: a randomized, double-blinded crossover trial. Issue 6 (1st July 2020) - Kristiansen, Oscar; Vethe, Nils Tore; Peersen, Kari; Wang Fagerland, Morten; Sverre, Elise; Prunés Jensen, Elena; Lindberg, Morten; Gjertsen, Erik; Gullestad, Lars; Perk, Joep; Dammen, Toril; Bergan, Stein; et al.
Abstract: Aims: To estimate the effect of atorvastatin on muscle symptom intensity in coronary heart disease (CHD) patients with self-perceived statin-associated muscle symptoms (SAMS) and to determine the relationship to blood levels of atorvastatin and/or metabolites. Methods and results: A randomized multi-centre trial consecutively identified 982 patients with previous or ongoing atorvastatin treatment after a CHD event. Of these, 97 (9.9%) reported SAMS and 77 were randomized to 7-week double-blinded treatment with atorvastatin 40 mg/day and placebo in a crossover design. The primary outcome was the individual mean difference in muscle symptom intensity between the treatment periods, measured by visual-analogue scale (VAS) scores. Atorvastatin did not affect the intensity of muscle symptoms among 71 patients who completed the trial. Mean VAS difference (statin-placebo) was 0.31 (95% CI: −0.24 to 0.86). The proportion with more muscle symptoms during placebo than atorvastatin was 17% ( n  = 12), 55% ( n  = 39) had the same muscle symptom intensity during both treatment periods whereas 28% ( n  = 20) had more symptoms during atorvastatin than placebo (confirmed SAMS). There were no differences in clinical or pharmacogenetic characteristics between these groups. The levels of atorvastatin and/or metabolites did not correlate to muscle symptom intensity among patients with confirmed SAMS (Spearman's rho ≤0.40, for all variables). Conclusion: Re-challenge with high-intensity atorvastatin did not affect the intensity of muscle symptoms in CHD patients with self-perceived SAMS during previous atorvastatin therapy. There was no relationship between muscle symptoms and the systemic exposure to atorvastatin and/or its metabolites. The findings encourage an informed discussion to elucidate other causes of muscle complaints and continued statin use.